Siege of Adrianopol during the first Balkan war (1912–1913) - Faszcza, Dariusz (City and War, 2021)
Every war is evil, bringing death, suffering, expulsion and havoc. During the two Balkan wars of 1912–1913, such events also took place, which on the one hand were characterized by a considerable intensity and variety of forms of military operations, and on the other hand, by unprecedented cruelty against civilians. The aim of the article is to present the conditions in which the defense of Adrianople was carried out during the First Balkan War. To achieve this goal, it was necessary to discuss the military significance of the Adrianople fortress and the course of siege, taking into account the situation of civilian population in besieged city.